2009
DOI: 10.1007/s11269-009-9405-6
|View full text |Cite
|
Sign up to set email alerts
|

Rainwater Harvesting for Urban Areas: a Success Story from Gadarif City in Central Sudan

Abstract: Gadarif city, in central Sudan, has suffered from a shortage of drinking water for decades. Half of its daily water requirement is met through river water imported over 50 km away and from local salty wells. As a consequence of building a small dam to control seasonal floods, it was found that the dam reservoir recharges groundwater, raising the water table by few a meters. Such experience was repeated and a second dam built in response to this success. This indicates that such a method may be a useful rainwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 19 publications
0
17
0
Order By: Relevance
“…Pachpute et al (2009) stated that sustainability of rainwater harvesting in enhancing water productivity in various biophysical and socioeconomic conditions of Sub-Saharan Africa (Makanya catchment) was a key in large scale livelihood improvement. Gadarif City of Sudan could improve the drinking water scarcity applying rainwater harvesting system in semi-arid regions affected by climate change and population increase (Ibrahim 2009). Ghisi (2009) made a study at the state of São Paulo, Brazil and concluded that rainwater harvesting could increase the efficiency if the rainwater tank sizing for houses could be designed for each specific situation, i.e., considering local rainfall, roof area, potable water demand, rainwater demand and number of residents.…”
Section: Introductionmentioning
confidence: 99%
“…Pachpute et al (2009) stated that sustainability of rainwater harvesting in enhancing water productivity in various biophysical and socioeconomic conditions of Sub-Saharan Africa (Makanya catchment) was a key in large scale livelihood improvement. Gadarif City of Sudan could improve the drinking water scarcity applying rainwater harvesting system in semi-arid regions affected by climate change and population increase (Ibrahim 2009). Ghisi (2009) made a study at the state of São Paulo, Brazil and concluded that rainwater harvesting could increase the efficiency if the rainwater tank sizing for houses could be designed for each specific situation, i.e., considering local rainfall, roof area, potable water demand, rainwater demand and number of residents.…”
Section: Introductionmentioning
confidence: 99%
“…In this context Zhang et al (2010) stated that a reduction of some 32% of the water use can be achieved by gray-water reuse and rainwater harvesting allows for a reduction of 25%. Ibrahim (2009) also found that rainwater harvesting can be a useful technique for providing safe water in water deficit areas in semi-arid regions.…”
Section: The House Of Tomorrowmentioning
confidence: 94%
“…The success of a 2009 RWH project by NetWater and its partners that installed RWH systems at 12 hospitals in Sri Lanka triggered a further 22 RWH applications by 2011 (Women for Water Partnership, 2012). In Central Sudan, Ibrahim (2009) reported on how the success of small RWH dams has encouraged the authorities to expand the RWH initiative as part of a long-term solution for the water supply in the city.…”
Section: Literature Reviewmentioning
confidence: 99%